Distributed Attack Detection For Wireless Sensor Networks - Annamalai Giri, A.; Mohan, E. (International Journal of Engineering and Technology, 2018)
Wireless sensor network when data are transmitting between devices may cyber attackers interfere and try to hack the data,   In order to avoid attackers we are proposing fusion center monitoring, which finding the attackers and communicating the   information to cluster head. Through cooperative detection method fusion head is alarming the neighbor nodes to avoid the   congestion. This proposed methodology is enhanced prevent the deduction for attack in wireless sensor networks.